1986
DOI: 10.1007/bf00453755
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of movement in outer hair cells and a possible structural basis

Abstract: Isolated outer hair cells were found to slowly shorten when subjected to a solution that would induce contraction in a muscle fibre. Two possible mechanisms underlying this behaviour emerge from ultrastructural and immunocytochemical investigations. Antibody labelling at the electron microscopic level demonstrates that actin is present not only in the stereocilia and in the cuticular plate but also along the wall of outer hair cells, between the plasma membrane and the subsurface fenestrated cisternae. The lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1
8

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(116 citation statements)
references
References 20 publications
7
100
1
8
Order By: Relevance
“…A variety of calcium-binding proteins are known to be present in the inner ear where they are thought to play diverse roles in transduction, motile response, and in neurotransmitter release (Rabie et al 1983;Dechesne et al 1991;Flock et al 1986;Slepecky and Ulfendahl 1993;Ichimiya et al 1994a,b). The large number of calcium-binding proteins in the present study was included because their individual characteristic distributions suggest that they serve different functions within the cochlea (e.g., Pack and Slepecky 1995;Imamura and Adams 1996).…”
Section: Cytochemical Effects Of Gentamicin Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of calcium-binding proteins are known to be present in the inner ear where they are thought to play diverse roles in transduction, motile response, and in neurotransmitter release (Rabie et al 1983;Dechesne et al 1991;Flock et al 1986;Slepecky and Ulfendahl 1993;Ichimiya et al 1994a,b). The large number of calcium-binding proteins in the present study was included because their individual characteristic distributions suggest that they serve different functions within the cochlea (e.g., Pack and Slepecky 1995;Imamura and Adams 1996).…”
Section: Cytochemical Effects Of Gentamicin Treatmentmentioning
confidence: 99%
“…In the present study immunostaining is used to assay for the following transport proteins: Na + ,K + -ATPase, the Na + ,Ca ++ exchanger, the membrane-bound Ca ++ -ATPases, plasma membrane calcium-ATPase (PMCA) and smooth endoplasmic reticulum calcium-ATPases SERCA1 and SERCA2, as well as carbonic anhydrase (CA), all of which play major roles in controlling intracellular ion content. A variety of calcium-binding proteins are known to be present in the inner ear where they are thought to play diverse roles, including but not limited to transduction, motile responses, and neurotransmitter release (Rabie et al 1983;Dechesne et al 1991;Flock et al 1986;Slepecky and Ulfendahl 1993;Ichimiya et al 1994a,b). The following calcium-binding compounds were assayed: peptide 19, calretinin, calbindin, S-100, osteopontin, calmodulin, and caldesmon.…”
Section: Introductionmentioning
confidence: 99%
“…We reacted whole mounts of the basilar papilla with antibodies to calmodulin, which have been shown to label hair cells selectively in the mature mammalian organ of Corti (Flock et al, 1986;Slepecky et al, 1988;Bauwens et al, 1991;Slepecky and Ulfendahl, 1993), and with the TUJ1 antibody, which labels class III ␤ tubulin in early differentiating neurons (Moody et al, 1989;Lee et al, 1990;Easter et al, 1993). In addition to examining the pattern of antibody labeling in the intact whole mounts, we embedded immunoreacted cochleae in plastic and sectioned them so that the cellular distribution of each antigen could be determined.…”
Section: Immunolabeling Of Hair Cells In Normal and Drugdamaged Cochlmentioning
confidence: 99%
“…a return of the hair cell to its original morphological and physiological condition upon withdrawal of the stimulus 255 (Brownell, 1984;Brownell et al, 1985;Zenner et al 1985b Responses to electrical stimuli (Brownell et al, 1985) as well as cytochemical reactions (Flock et al, 1986) have been demonstrated in cells that appear degenerating by the morphological criteria spelled out above. It would seem, however, that cells with good morphology and viability are more likely to yield experimental results unperturbed by artifacts.…”
Section: Degenerationmentioning
confidence: 99%